Impact of Performance Audit on Public Organisations: The Study of The Indonesian Central Government - Amien, Aditya Rizaldi (2020)
Compared to the traditional financial and compliance audit, performance audit is a relatively new innovation that emerges amidst the escalating concern to public accountability. Government corruption, Economic distress, and public service inefficiency are considered as the catalyst that motivates the general public to demand better performance and greater accountability in the public sector. One instrument to fulfil the public demand is by implementing the performance audit. The practice of performance audit in Indonesia was mandated to Badan Pemeriksa Keuangan (BPK) that act as the Indonesian Supreme Audit Organisation. Since the performance audit has been performed in Indonesia in since two decades ago the study will try to examine to what extent the performance audit has generated impact to the audited organisation namely the Economic Ministries in Indonesia. The study limits the performance audit period conducted from 2012-2017. The impact was measured using the perceptions of staff of the audited organisation which captured using survey instrument employing a five-category Likert-type scale. A total of 75 questionnaires were distributed and 51 feedback was received and considered valid. The findings of the study are quite surprising since it displayed a significant impact was experienced by the auditees. The results substantially differ with the prior research conducted in the context of Pan-Canadian and Scandinavian public sector which only shows trivial and minimal impact. Although the auditees perception considered to be more objective, it should also be considered as the study limitation since there is a possibility of the respondents to embellish the fact with the tendency to minimise or maximise the influence that auditors might have on them. Since the study of measurement of performance audit impact on the public organisation is not widely available, this study will enrich the literature of performance audit especially in the context of the Indonesian public sector.